How Much Does a Private School Student Count? A Critical Analysis of the Athletic Multiplier - James, John T. (Catholic Education: A Journal of Inquiry and Practice, 2007)
As Catholic high schools continue to experience success in interscholastic athletic leagues, state associations have repeatedly contemplated ways to thwart the perceived Catholic school advantage. One such effort, the multiplier, receives critical assessment in this article.